Isozymic forms of rat brain Ca2+-activated and phospholipid-dependent protein kinase. - Huang, K P (1986)
Three forms of rat brain Ca2+-activated and phospholipid-dependent protein kinase (EC 2.7.1.37) were separated by hydroxylapatite column chromatography. These enzymes, designated type I, II, and III protein kinase C, all have a molecular weight of 82,000, undergo autophosphorylation in the presence of Ca2+, phosphatidylserine, and diolein, and bind [3H]phorbol 12,13-dibutyrate. Autophosphorylation of these kinases resulted in an incorporation of 1-1.5 mol of 32P per mol of enzyme. Two-dimensional peptide mapping analysis revealed that these kinases had different sites of autophosphorylation. Phosphoamino acid analysis showed that type I and type III protein kinase C primarily autophosphorylated at a serine residue, whereas type II kinase autophosphorylated at both serine and threonine residues. In addition, polyclonal antibodies raised against a mixture of three types of the kinase preferentially inhibited type I and type II enzymes. Monoclonal antibodies against type I and type II kinase only recognized their respective enzymes but not the type III enzyme. These results demonstrate the presence of isozymic forms of protein kinase C in rat brain.